El Clima Organizacional y el desempeño laboral de los GAD del subtrópico Bolívar, año 2018 - Ramos Bonilla, María José (2018)
To achieve optimal functioning within public institutions it is very important that there is an organizational climate full of harmony, this element has a direct influence on job performance, so it is very important to dedicate effort to know and tend to the satisfaction of talent human in his work environment. Therefore, the following research project called "Organizational Climate and Labor Performance of Subdivisional GAD of Bolívar Province, year 2018" is proposed. Within Chapter 1, the problem called "How the organizational climate influences the performance of the subadult Bolivar's GAD staff" is addressed initially, and then start to make a coherent justification and highlight the importance, relevance, feasibility and the impact that this research will have on the GADs of the subtropical province of Bolívar, for which the following general objective is proposed: "Assess the organizational climate and the work performance of the GADs of the Bolivar subtropics". Within Chapter 2, the theoretical framework is addressed, which is composed of the scientific, conceptual, legal and referential theory, which are intended to give a theoretical basis to the research project and its variables within which It deals with information regarding the organizational climate, such as measuring the organizational climate, tools for measuring the organizational climate, work performance, the same that has been taken from different authors and bibliographic sources. Chapter 3 deals with the methodology under which the present research project is immersed, the methods used are Inductive, Deductive, Analytical and Comparative, in a consecutive way, the types of research framed within the project are established. which highlights Exploratory, Descriptive and Research-Action, then establishes the techniques and instruments for obtaining data, as primary source the survey and direct observation are used, in the same way because the universe is very large within of the GAD's research motives, the formula was applied to obtain the sample to be surveyed, obtaining the following data: 113 employees between administrative and operative within the GAD Caluma, 104 employees between administrative and operative within the GAD Echeandía and 75 employees between administrative and operative a to be surveyed within GA Las Naves, in a short It analyzes and interprets the results of the 30 surveys conducted at the GAD of Caluma, Echeandía and Las Naves and an analysis comparing the results obtained in each GAD surveyed on the organizational climate and the work performance of its employees. As a general conclusion, it is found that a weak point in the GADs investigated is the instability of their employees, in the same way it was found that there are certain deficiencies in the communication between the employees and the immediate boss, in the same way it was identified that there are certain shortcomings in the accuracy and compliance of the planned activities, in the same way there are certain employees who do not know the objectives of their departments, as well as it was determined that they do not have the security measures for the fulfillment of their functions. The present investigation determined in the same way that the GAD that provides better conditions to its employees in terms of the organizational climate and work performance, is the GAD of Caluma and the one that provides the worst conditions is the GAD of Las Naves, finding that the GAD of Echeandía is on average. After the analysis and interpretation of results, the proposal to the present research project named "Operational Plan of improvement of the organizational climate and the work performance of the investigated GADs" is presented, the same one that proposes strategies that seek to solve the problems found within the GADs investigated.